Higher-order cumulants and correlation functions of proton multiplicity distributions in √ s N N = 3 GeV Au + Au collisions at the RHIC STAR experiment - STAR Collaboration (Physical Review C, 2023)
We report a measurement of cumulants and correlation functions of event-by-event proton multiplicity distributions from fixed-target Au+Au collisions at √sNN = 3 GeV measured by the STAR experiment. Protons are identified within the rapidity (y) and transverse momentum (pT) region −0.9<y<0 and 0.4<pT<2.0 GeV/c in the center-of-mass frame. A systematic analysis of the proton cumulants and correlation functions up to sixth order as well as the corresponding ratios as a function of the collision centrality, pT, and y are presented. The effect of pileup and initial volume fluctuations on these observables and the respective corrections are discussed in detail. The results are compared to calculations from the hadronic transport UrQMD model as well as a hydrodynamic model. In the most central 5% collisions, the value of proton cumulant ratio C4/C2 is negative, drastically different from the values observed in Au+Au collisions at higher energies. Compared to model calculations including lattice QCD, a hadronic transport model, and a hydrodynamic model, the strong suppression in the ratio of C4/C2 at 3 GeV Au+Au collisions indicates an energy regime dominated by hadronic interactions.
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed